Sustained high plasma mannose less sensitive to fluctuating blood glucose in glycogen storage disease type Ia children. Issue 1 (13th September 2012) - Nagasaka, Hironori; Yorifuji, Tohru; Bandsma, Robert H. J.; Takatani, Tomozumi; Asano, Hisaki; Mochizuki, Hiroshi; Takuwa, Mayuko; Tsukahara, Hirokazu; Inui, Ayano; Tsunoda, Tomoyuki; Komatsu, Haruki; Hiejima, Eitaro; et al.
Abstract: Plasma mannose is suggested to be largely generated from liver glycogen‐oriented glucose‐6‐phosphate. This study examined plasma mannose in glycogen storage disease type Ia (GSD Ia) lacking conversion of glucose‐6‐phosphate to glucose in the liver. We initially examined fasting—and postprandial 2 h—plasma mannose and other blood carbohydrates and lipids for seven GSD Ia children receiving dietary interventions using cornstarch and six healthy age‐matched children. Next, one‐day successive intra‐individual parameter changes were examined for six affected and two control children. Although there were no significant differences in fasting—and postprandial 2 h—glucose and insulin levels, the mannose level of the affected group was invariably much higher than that of the control group ( p  < 0.001): the fasting level of the affected group was about two‐fold that of the control group; the postprandial‐2 h level remained almost unchanged in the affected group, although it was one‐half of the fasting level in the control group. Inter‐individual analyses revealed that the GSD Ia group mannose level was significantly and positively correlated with lactate and triglycerides levels at both time points ( p  < 0.01). In each control, mannose levels fluctuated greatly, maintaining strong and significant negative correlations with glucose and insulin levels ( p  < 0.001). Correlations were lower or nonexistent in GSD Ia children. In individuals with high lactate and triglycerides levels, strikingly high mannose levels never changed against glucose and insulin fluctuations. Plasma mannose is less sensitive to blood glucose and insulin in GSD Ia children. Its basal level and the fluctuation pattern differ by their metabolic activity.